OPERE MENİNGOMİYELOSELLİ HASTALARDA BÖBREK FONKSİYONLARININ DEĞERLENDİRİLMESİ - KILAVUZ, FATİH (Fırat Üniveristesi, 2020)
Spina bifida gebelikte ilk haftalarda nöral kanalın tam kapanamaması sonucu sinirlerin ve meninkslerin protrüzyonuna sebep olan bir doğum defektidir. Miyelomeningosel (MMC) spina bifidanın ağır bir formu olup, spinal kordun bir tabakası orta hat defektinden dışarıya bir kese olarak herniye olur. Bu vakalarda görülen nefrolojik ve ürolojik patolojiler de oldukça farklılık göstermektedir. Miyelomeningoselli hastalarda uyumsuz ve retrakte mesane, idrar inkontinansı, üriner sistem taşları, idrar yolu enfeksiyonları, nörojenik mesane, vezikoüreteral reflü (VUR) ve kronik böbrek yetmezliği (KBY) görülebilmektedir. Bu çalışmada amaç opere meningomiyeloselli hastalarda böbrek fonksiyonlarının değerlendirilmesidir. Bu çalışma Şubat 2019 ve Haziran 2020 tarihleri arasında Fırat Üniversitesi Hastanesi'nde yapılmıştır. Çocuk nöroloji ve çocuk nefroloji polikliniğine başvuran opere olmuş meningomiyeloselli toplam 34 çocuk çalışmaya alındı. Kontrol grubu olarak da çocuk sağlığı ve hastalıkları polikliniğine başvuran, akut ve kronik hastalığı olmayan ve ilaç kullanmayan, demografik özellikleri hasta grubuna benzeyen 4-17 yaş arası 34 sağlıklı çocuk alındı. Başvuru anında tüm hastaların tam kan sayımı, tam idrar tetkiki, kanda sodyum, potasyum, klor, kalsiyum, fosfor, magnezyum, ürik asit, kreatinin ve üre, spot idrarda sodyum, potasyum, kreatinin, fosfor, klor, ürik asit, magnezyum, kalsiyum, protein ve üre düzeylerine bakıldı. Yine tüm hastaların kan ve idrarında renal parankimal hasarın göstergesi olan nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF) ve neutrophil gelatinase-associated lipocalin (NGAL) molekülü değerlerine bakıldı. Hasta grubunun serum NGF düzeyleri kontrol grubundan anlamlı düzeyde yüksek bulundu (p=0,003). Hasta grubu ile kontrol grubu arasında serum BDNF ve serum NGAL seviyesi açısından anlamlı bir farklılık saptanmadı (p>0,05). Hasta grubu ile kontrol grubu arasında idrar NGF, BDNF ve NGAL düzeyi açısından anlamlı bir ilişki tespit edilmedi (p>0,05). Sonuç olarak hasta grubunun serum NGF düzeyleri kontrol grubundan anlamlı düzeyde yüksek bulundu. Miyelomeningoselli hastalarda özellikle serum BDNF, NGAL ve idrar NGF, BDNF ve NGAL düzeylerinin araştırıldığı daha kapsamlı çalışmalara ihtiyaç olduğu düşünüldü.

Spina bifida is a birth defect causing the protrusion of the nerves and meninges as a result of the improper closure of the neural tube during the early weeks of gestation. Myelomeningocele (MMC) is a severe form of spina bifida, where a layer of the spinal cord is herniated outwards from the midline defect as a sac. The nephrological and urological pathologies observed in such cases also vary. In patients with myelomeningocele, bladder noncompliance and retraction, urinary incontinence, urinary stones, urinary tract infections, neurogenic bladders, vesicoureteral reflux (VUR) and chronic renal failure (CRF) can be observed. In this study, it is aimed to evaluate the renal functions in operated patients with meningomyelocele. This study was conducted in Firat University Hospital between February 2019 and June 2020. A total of 34 children, who were diagnosed with meningomyelocele and underwent surgery, and who presented to the departments of pediatric neurology and pediatric nephrology were included in the study. The control group was comprised of 34 healthy children aged between 4 and 17, who had applied to the department of pediatrics, had no acute or chronic diseases and used no medication, and whose demographic characteristics resembled those of the patient group. During the admission, patients' complete blood counts, complete urinary values, sodium, potassium, chlorine, calcium, phosphor, magnesium, uric acid, creatinine and urea levels in blood, sodium, potassium, creatinine, phosphor, chlorine, uric acid, magnesium, calcium, protein and urea levels in spot urine were examined. Moreover, nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF) and neutrophil gelatinase-associated lipocalin (NGAL) molecule values, which are the indicators of renal parenchymal damage, were checked in the blood and urine of all the patients. The serum NGF levels of the patient group were found significantly higher than those of the control group (p=0.003). No significant difference was detected between the patient group and the control group in terms of serum BDNF and serum NGAL levels (p>0,05). No significant correlation was discovered between the patient group and the control group in terms of urine NGF, BDNF and NGAL levels (p>0,05). Consequently, the serum NGF levels of the patient group were found to be significantly higher than those of the control group. We believe that more comprehensive studies are needed especially to research serum BDNF, NGAL and urine NGF, BDNF and NGAL levels in patients with myelomeningocele. Key Words: Meningomyelocele, spina bifida, NGF, BDNF, NGAL
Evaluation of kidney functions in operated meningomyelocella patients
Keywords: Çocuk Sağlığı ve Hastalıkları